GREEN INTELLECTUAL CAPITAL, ESG, CARBON EMISSION DISCLOSURE, AND FIRM VALUE IN ENERGY FIRMS - Syamsul Bahri; Windu Mulyasari; Ina Indriana (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study examines the effect of Green Intellectual Capital Disclosure on firm value and tests whether ESG Disclosure and Carbon Emission Disclosure mediate this relationship. Research Methodology: The study uses a quantitative explanatory design with secondary data from annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange during 2020-2023. The final sample consists of 189 firm-year observations. Panel regression with random effects and Sobel tests were processed using Stata 17. Results: Carbon Emission Disclosure has a positive and significant effect on firm value, whereas Green Intellectual Capital Disclosure and ESG Disclosure do not have direct significant effects. Green Intellectual Capital Disclosure significantly increases ESG Disclosure and Carbon Emission Disclosure. The mediation test confirms Carbon Emission Disclosure as a significant mediator, while ESG Disclosure is not significant. Conclusions: Carbon transparency is the most effective signaling channel through which green knowledge resources are translated into higher firm value in the Indonesian energy sector. Limitations: The study is limited by the availability of complete sustainability data and by content-analysis measures that primarily capture disclosure quantity. Contributions: The study contributes to signaling theory and provides practical insight for managers, investors, and regulators concerning the market relevance of carbon disclosure.